Analisis Dividend Policy Perusahaan LQ-45 di Bursa Efek Jakarta - Joko, Fx Agus (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2006)
The objective of this research is to investigate dividend policy of go public companies in IQ45 on Jakarta Stock Exchange. The sources of data steemfr om financial report of 45 companies from 2000 to 2N2. Variables to measure consist of dependent variable (dividend payout ratio) and ir&pendent variable (firm size, growth of operating income, cosh flow variability , capital structure/flexibility). Satistical ndelw by lineu regressiur with degree ol confidence 5%o to F test ed t test we used to test of the lWhotesis. The reslt sttows tlnt p*ttally each irdcperden vsioble intluerces signific@rtly to diviM p-isa yout ratlo. Simultaneously, all indepetdent vsiables influence divided payout rdio. K vslue g.meming to wy tlat 77.3% chnging in &perden vwiable (divided palaut ratio) cnt be erytaircdtlw irdeperdentv qiables. The rest o f that value ,which is 22.7%0te, by other variables outside mdel.